Comparison of bacterial communities in sponge, sediment and water biotopes in the Indo-Pacific region - Pires, Ana Cecília da Cruz (2021)
Sponges are an important structural and abundant part of coral reefs, and their microbial symbionts contribute to nutrient cycling and host nutrition, health and defence. However, microbial communities associated to sponges have to be structurally and functionally characterized so their symbiotic function in such host can be truly understood. This thesis addresses, through the use of a 16S rRNA gene high-throughput sequencing approach, the analyses of the composition, phylogeny and putative functions of bacterial communities inhabiting the sponges Suberites diversicolor, Cinachyrella australiensis, Stylissa carteri, Stylissa massa, Aaptos lobata and Xestospongia testudinaria and both seawater and sediment from three different systems (Indonesian marine lakes and coral reefs from Singapore and Tioman) in the Indo-Pacific region. Also, the influence of habitat (e.g. marine lake vs. open water) on bacterial composition and the influence of HMA/LMA dichotomy on putative function of sponge-associated bacteria were evaluated. Results showed, in general, biotope as the main predictor of bacterial communities’ richness, composition, abundance and putative function. Significant differences were found between sponges’ bacterial communities and those from the surrounding seawater and sediment. Habitat only appeared to be a better predictor than biotope for bacterial richness in marine lakes. Strong similarities were detected between bacterial communities in X. testudinaria and the putative HMA A. lobata, supporting the previous indication that A. lobata might be indeed an HMA sponge. Moreover, all samples were dominated by phyla involved in nutrient cycling and in sponge nutrition, health and defence, such as Proteobacteria, Chloroflexi and Cyanobacteria. At a lower taxa level, samples were dominated by Kiloniellales (with potential for denitrification), Chromatiales (purple sulphur bacteria), Hyphomicrobiaceae (methylotrophic denitrifiers), SRA202 (sulphite-oxidizers), Anaerolineae (organic matter degraders), Synechococcophycideae (carbon fixation), Thiohalorhabdales (sulphur oxidizing bacteria). The predicted metagenome (PICRUSt) analysis showed high similarity of functional profiles between both Stylissa species and between A. lobata and X. testudinaria. Furthermore, subcategories “Signaling Molecules and Interaction”, “Carbohydrate Metabolism” and “Excretory System” were enriched in HMA sponges whilst subcategories “Replication and Repair”, “Energy Metabolism”, “Metabolism of Cofactors and Vitamins” and “Environmental Adaptation” were enriched in LMA sponges. The results also showed that HMA and LMA associated bacterial communities shared similar core functional features, albeit they use distinct strategies to deal with pathogens, obtain energy or DNA repair against environmental stress.